Analisis kemampuan argumentasi matematis siswa pada materi bangun ruang sisi datar ditinjau dari kemampuan awal matematika - Lubis, Mara Samin; Lubis, Nur Ainun (Jurnal Pengembangan Pembelajaran Matematika (JPPM), 2024)
The aim of the research is to determine the level of students' argumentation ability to solve surface area and volume problems based on students' initial mathematical abilities. This research focused to discover new things that students do in solving problems based on the level of Toulmin argumentation ability. The methodology for taking subjects in this research was purposive, namely by categories of students with high, medium and low abilities, looking at the students' report cards. Students with a high level of initial argumentation can state claims, evidence and reasoning well but are less able to provide rebuttals. Students with a medium initial level of argumentation are only able to state claims and data well. Meanwhile, students with a low level of initial argumentation always make wrong claims and are not able to show evidence, reasoning and rebuttal to support their claims. High entry level students' argumentation abilities are at level 2 except for the rebuttal component, the rebuttal component is at level 0 where students tend to be unable to make counterclaims and unable to reject false statements. Students' argumentation abilities are not all students' initial argumentation abilities are at level 1, where students' ability to make claims and evidence is at level 2 while the ability to make rebuttals is at level 0. Students' initial argumentation abilities are low at level 0 where students are not able make claims, evidence, reasoning, and rebuttal well.